2004
DOI: 10.1038/sj.cdd.4401470
|View full text |Cite
|
Sign up to set email alerts
|

The vital osteoclast: how is it regulated?

Abstract: Bone is a rigid but dynamic organ. Once formed, it is continually broken down and reformed by the co-ordinated actions of osteoclasts (that mediate resorption) and osteoblasts (that mediate formation) on trabecular bone surfaces and in the Haversian systems of cortical bone. Any net change in bone mass therefore reflects a change in the balance between these two processes. If osteoclastic bone resorption exceeds the bone-forming capacity of osteoblasts, the result is osteoporosis, but if the opposite occurs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
(17 reference statements)
0
24
0
1
Order By: Relevance
“…In addition to RANKL-[Ca 2+ ] i oscillation-NFATc1 pathway, Rgs12 also regulates c-fos expression; this suggested that Rgs12 may be involved in RANKL-JNK-c-Fos pathway. 43 Overexpression of NFAT2 partially restored the differentiation ability and Cathepsin K expression but not c-Fos expression in Rgs12-deficient OC precursor cells. This is supported by the findings from Takayanagi et al that NFAT2 cooperates with c-Fos to lead to OC differentiation and that overexpression of NFAT2 can only partially restore the osteoclastogenesis in NFAT2-mutant cells.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to RANKL-[Ca 2+ ] i oscillation-NFATc1 pathway, Rgs12 also regulates c-fos expression; this suggested that Rgs12 may be involved in RANKL-JNK-c-Fos pathway. 43 Overexpression of NFAT2 partially restored the differentiation ability and Cathepsin K expression but not c-Fos expression in Rgs12-deficient OC precursor cells. This is supported by the findings from Takayanagi et al that NFAT2 cooperates with c-Fos to lead to OC differentiation and that overexpression of NFAT2 can only partially restore the osteoclastogenesis in NFAT2-mutant cells.…”
Section: Discussionmentioning
confidence: 94%
“…The MHA adsorbed OPG in specific pH environments exhibits a sustained release pattern in this acid environment (Scheme 2). The activation of RANK would be prevented by OPG binding to RANKL and OPG can also induce apoptosis of osteoclast [33][34][35].…”
Section: Langmuir and Freundlich Models For Bsa Adsorption And Releasmentioning
confidence: 99%
“…The local pH around the ruffled border of osteoclasts is from 4.0 to 5.0 [31,32]. Osteoprotegerin (OPG), which belongs to the tumor necrosis factor (TNF) receptor superfamily [33], is known to negatively regulate osteoclast maturation and activation and to promote apoptosis [33][34][35]. Realizing the controlled release of OPG under acid conditions is very promising.…”
Section: Introductionmentioning
confidence: 99%
“…One example is OPG, which belongs to the tumor necrosis factor (TNF) receptor superfamily [32]. OPG is known to negatively regulate osteoclast maturation and activation [1]. This factor initially acts as a decoy receptor and prevents the interaction of RANKL with RANK, thereby curbing the activity, survival, and proliferation of osteoclasts [22].…”
Section: Introductionmentioning
confidence: 99%